Мы с приятелем : стихи / Сергей Михалков ; худ. А. Чижиков - Михалков Сергей Владимирович (Почитай мне стихи, 2007)
Экземпляры: (201110) / Инвентарный номер: / Цена: 6.00 / Сис.шифр: Д / Авт.знак: М 69 / ББК: Д